Today's Technician: Automotive Electricity & Electronics - Hollembeak Barry (Thomson Delmar Learning, 2006)
The newest edition of this classroom and shop manual set continues to provide unsurpassed coverage of the theory and procedures for automotive electricity and electronics. Streamlined diagnostic and service procedures and added attention to data bus networks, including the CAN, LIN, ISO, and other common systems, are highlighted in this revision. Expanded coverage of vehicle accessory systems includes the new multi-stage air bag systems, weight classification systems, side air bag systems, and laser guided cruise control systems. An all-new chapter on hybrid and high voltage systems is also featured.